Chemical-free transfer of patterned reduced graphene oxide thin films for large area flexible electronics and nanoelectromechanical systems. (22nd September 2020) - Patil, Nikhil; Gupta, Aparna; Jaiswal, Manu; Dutta, Soumya
Abstract: In this paper, a wet-dry hybrid technique to transfer patterned reduced graphene oxide (rGO) thin film to arbitrary substrates at predetermined locations without using any chemicals is reported. The transfer process involves water-assisted delamination of rGO, followed by dry transfer to an acceptor substrate using viscoelastic stamp. Patterned reduced graphene oxide films are transferred to silicon dioxide (SiO2 /Si) substrate to begin with. Subsequently, the method is deployed to transfer rGO to different polymer substrates such as poly(methyl methacrylate) (PMMA), and crosslinked poly(4-vinylphenol) (c-PVP), which are commonly used as gate dielectric in flexible electronic applications. The credibility of the transfer process with precise spatial positioning on the target substrate leads to fabrication of freely suspended reduced graphene oxide membrane towards nanoelectromechanical systems (NEMS) based devices such as nanomechanical drum resonators.